Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

What is the inverse of [tex]$f(x)=3 x^3-4$[/tex]?

A. [tex]f^{-1}(x)=\frac{x+1}{3}[/tex]

B. [tex]f^{-1}(x)=\sqrt[2]{\frac{x+4}{3}}[/tex]

C. [tex]f^{-1}(x)=3 x+4[/tex]

D. [tex]f^{-1}(x)=\sqrt{\frac{x+4}{3}}[/tex]


Sagot :

To find the inverse of the function [tex]\( f(x) = 3x^3 - 4 \)[/tex], we need to follow a systematic approach:

1. Start by replacing [tex]\( f(x) \)[/tex] with [tex]\( y \)[/tex]:
[tex]\[ y = 3x^3 - 4 \][/tex]

2. Solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:

- Step 1: Add 4 to both sides of the equation:
[tex]\[ y + 4 = 3x^3 \][/tex]

- Step 2: Divide both sides by 3:
[tex]\[ \frac{y + 4}{3} = x^3 \][/tex]

- Step 3: Take the cube root of both sides to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \left( \frac{y + 4}{3} \right)^{\frac{1}{3}} \][/tex]

3. Replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] to express the inverse function [tex]\( f^{-1}(x) \)[/tex]:
[tex]\[ f^{-1}(x) = \left( \frac{x + 4}{3} \right)^{\frac{1}{3}} \][/tex]

Thus, the inverse function is [tex]\( f^{-1}(x) = \left( \frac{x + 4}{3} \right)^{\frac{1}{3}} \)[/tex].

Comparing this with the given options:
- A) [tex]\( f^{-1}(x) = \frac{x+1}{3} \)[/tex]
- B) [tex]\( f^{-1}(x) = \sqrt[2]{\frac{x+4}{3}} \)[/tex]
- C) [tex]\( f^{-1}(x) = 3x + 4 \)[/tex]
- D) [tex]\( f^{-1}(x) = \sqrt{\frac{x+4}{3}} \)[/tex]

We see that none of the options exactly match the derived inverse. The correct expression derived for the inverse function does not perfectly align with any of the provided multiple choices.